CPC-016 Analysis of Pharmacists' Interventions on Inpatient Prescriptions and a Consideration of the Role of Hospital Pharmacists. (12th March 2013) - Cho, Y; Kim, HS; Lee, JY; Kwon, KH; Shin, YG
Abstract : Background: The hospital pharmacist's role has changed steadily and is turning away from dispensing functions toward active involvement in pharmaceutical care. Intensifying verification of the prescriptions by dispensing pharmacists can contribute to improving the drug treatment of many more patients. Therefore, the system of inpatient prescription review by dispensing pharmacists was developed. Collaborative clinical pharmacist services in inpatient care have generally resulted in improved care and interaction with the health care team on patient rounds, patient interviews, medicines reconciliation, patient discharge counselling and follow-up. All these have resulted in improved outcomes. Purpose: The purpose of this study was to examine the record of interventions by pharmacists who didn't use a prescription review programme, the record of interventions by pharmacists who did use this programme, and the record of interventions by clinical pharmacists who participated in rounds. Thereafter, the purpose was to discuss the necessity for a change of role of hospital pharmacists. Materials and Methods: A retrospective study, analysis of intervention records by prescription error, type of pharmacist intervention, the significance of error, chi-square test SPSS v19, p < 0.05. Significance was classified as B2: could have resulted in significant morbidity or mortality if not prevented; B3: low potential for negative patient outcome. Results: The rates of pharmacist intervention in the three groups were 0.3%, 0.4% and 0.7%. Considerably different results were shown in the three groups of records on the types of prescription error, the type of pharmacist intervention and the significance of the error. The percentages of significance B2 in three groups were 28%, 37%, 80%, and those of B3 were 72%, 63%, 20%. Conclusions: In view of the results so far achieved especially in the significance of error, the role of clinical pharmacists participating in rounds has had a much more significant therapeutic effect on inpatients. The addition of clinical pharmacist services collaboratively in the care of inpatients generally resulted in improved care. Interacting with the health care team on patient rounds, interviewing patients, medicines reconciliation, and providing patient discharge counselling and follow-up have all resulted in improved outcomes. So, continuing efforts on effectiveness of all kinds of hospital pharmacists' work, such as automation of dispensing, are necessary. No conflict of interest.